CIMPACT‐NOW update 6: new entity and diagnostic principle recommendations of the cIMPACT‐Utrecht meeting on future CNS tumor classification and grading. (19th April 2020) - Louis, David N.; Wesseling, Pieter; Aldape, Kenneth; Brat, Daniel J.; Capper, David; Cree, Ian A.; Eberhart, Charles; Figarella‐Branger, Dominique; Fouladi, Maryam; Fuller, Gregory N.; Giannini, Caterina; Haberler, Christine; et al.
Abstract: cIMPACT‐NOW (the Consortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy) was established to evaluate and make practical recommendations on recent advances in the field of CNS tumor classification, particularly in light of the rapid progress in molecular insights into these neoplasms. For Round 2 of its deliberations, cIMPACT‐NOW Working Committee 3 was reconstituted and convened in Utrecht, The Netherlands, for a meeting designed to review putative new CNS tumor types in advance of any future World Health Organization meeting on CNS tumor classification. In preparatory activities for the meeting and at the actual meeting, a list of possible entities was assembled and each type and subtype debated. Working Committee 3 recommended that a substantial number of newly recognized types and subtypes should be considered for inclusion in future CNS tumor classifications. In addition, the group endorsed a number of principles—relating to classification categories, approaches to classification, nomenclature, and grading—that the group hopes will also inform the future classification of CNS neoplasms.